Geoffrey Andrew Holmes, Compiled Ordinances of the City of Council Bluffs 168-169 (1887) - (:unkn) unknown (My University, 1887)
§ 5-6: Prohibited operating a pistol gallery or shooting gallery without a license. Licenses shall cost ten dollars per month or fifty dollars per year. Minors are prohibited at the ranges.
Keywords: SHOOTING RANGES OR GALLERIES